1α,25-Dihydroxyvitamin D3 reduces uropathogenic E. coli persistence in bladder epithelial cells by restoring lysosome acidification (Bangladesh Journal of Pharmacology, 2025)
This study aimed to examine the effect of 1α,25-dihydroxyvitamin D3 [1,25(OH)2D3] on the intracellular persistence of uropathogenic Escherichia coli. After establishing a cell infection model and conducting drug intervention, methods such as fluorescent probes, Western blot, and qPCR were used. The results showed that 1,25(OH)2D3 (10 nM) reduced the number of persistent E. coli (at 12 and 24 hours) (P